Hubungan Social Competence Dengan Intensi Berwirausaha Mahasiswa Program Studi Manajemen Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta - Ocie Paramastuti, Belinda, Susatyo Yuwono ,S. Psi, M. Si., Psi (2017)
The purpose of this research: to examine the relationship of social competence among entrepreneurship intention. The population in this research is Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta from 2014 and 2015 amounted 850 students. The samples in the research using accidental sampling, the samples in this research are set as many 90 students. Data collection the research uses a measuring instrument Social Competence scale and Entrepreneurship Intetion scale, then it would be calculation of the data analysis using a technique analysis product moment spss 16.0 program. Based on this research there is a positive relationship between social competence among entrepreneurship intensions student of Program Studi Menejemen Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta. The results of this research showed 18,5% effective contribution of social competence toward entrepreneurship intention. While variations of entrepreneurship intention is explained by other factors outside the model is 81,5%. The categorization shows that the level of social competence of students is moderate and the level of students' intension is low.